Design and Development of an E-Commerce Management System: State of Places - Bailoul, Youusef; Khaldi, Mohamed (RA Journal of Applied Research, 2021)
In this work, we are interested in exchange relations and in particular e-mailing. Our goal is to provide a research methodology for the design and development of an e-commerce management system based on e-mailing. Thus, we define the e-commerce concept by providing a historical overview and by defining the different varieties of seller-buyer relationships and comparing it to the e-business concept. Then, we define the basic concepts of e-mailing, the benefits of a quality e-mailing, then we define the e-mailing software and their characteristics by proposing software examples. Finally, we propose a research methodology for the design and development of an e-commerce management system.